Biomaterials in tissue repair and regeneration: key insights from extracellular matrix biology - Abolhasani, Sakhavat; Ahmadi, Yasin; Rostami, Yavar; Baravar, Erfan; Fattahi, Davood (Frontiers in Medical Technology, 2025)
The extracellular matrix (ECM) serves as a dynamic biological framework that orchestrates cellular behavior through biomechanical and biochemical cues, playing a pivotal role in tissue homeostasis and repair. Despite significant advancements in biomaterial design, current regenerative strategies often fail to fully replicate the ECM's complexity, leading to suboptimal healing outcomes. This review comprehensively examines ECM biology and its application in biomaterial engineering, highlighting structural-functional relationships, integrin-mediated signaling, and ECM remodeling mechanisms in wound healing. We analyze diverse biomaterial classes—including ECM-based scaffolds, synthetic polymers, natural biomaterials, bioceramics, and composites—focusing on their design principles, fabrication techniques, degradation profiles, and clinical applications. Key challenges such as immunogenicity, vascularization, mechanical mismatch, and regulatory hurdles are critically evaluated. Innovations in decellularization, biofunctionalization, and advanced manufacturing (e.g., 3D bioprinting, electrospinning) are discussed as promising avenues to enhance biomimicry and therapeutic efficacy. Furthermore, we explore clinically approved ECM-derived products and underscore the need for standardized protocols to bridge translational gaps. By integrating emerging research with clinical perspectives, this review provides a roadmap for developing next-generation ECM-inspired biomaterials that address unmet needs in regenerative medicine, emphasizing interdisciplinary collaboration to optimize safety, functionality, and patient outcomes.